(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
This Hard turning finds a broad range of applications in manufacturing industries. The high wear resistance along with high dimensional accuracy is the primary attributes of the process. However, the critical setback associated with hard turning is the high heat generation at the cutting zone. It lead to earlier tool wear rate and causes the decrease in the machining performance. The cutting tool material plays a significant role in deciding the performance of hard turning. Therefore in this research work, an attempt has been made to investigate the performance of TiN coated CBN tools during machining of variable hardened AISI 4340 steel. The cutting speed, feed rate, workpiece hardness and cutting tools (uncoated CBN and TiN coated CBN) were selected as process parameters during experimentation. The cutting force, chip-tool interface temperature and material removal rate (MRR) was selected as performance parameters. The L-18 orthogonal array from Taguchi approach was chosen to perform the experimental work. The grey relational technique was used to optimize the process parameters. The results from the grey relational model were verified by using fuzzy logic. The experimental results indicate that tool material and feed rate are the significant process variables which influence the machining performance.